Comparison of angular factors to determine quickness in seoi-nage between elite and college judo athletes - Ishii, T.; Suzuki, Y.; Kobayashi, Y.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to identify factors to determine the quickness of a Seoi-nage by comparing the kinematic parameters during the Kuzushi and Tsukuri phases between elite and college Judo athletes. Three-dimensional data were collected on seoi-nage performed by three male elite judo athletes and seven male local college athletes using a three-dimensional motion analysis technique. This study found that the angular velocity of the upper limb of elite judo athletes was much faster than that of the college athletes. The elite athletes performed Seoi-nage with a technique in which they rotated lower body first, and then upper body so that the rotation of the upper limb was minimized in the early part of the turning phase. This finding can help teaching of a quick seoi-nage.